Acute right insular ischaemic lesions and poststroke left ventricular dysfunction - Winder, Klemens; Villegas Millar, Carolina; Siedler, Gabriela; Knott, Michael; Dörfler, Arnd; Engel, Anna; Achenbach, Stephan; Hilz, Max-Josef; Kallmünzer, Bernd; Schwab, Stefan; Seifert, Frank; Fröhlich, Kilian (Stroke and Vascular Neurology, 2023)
IntroductionMyocardial injury related to acute ischaemic stroke is common even without primary cardiac disease. We intended to determine associations between values of left ventricular ejection fraction (LVEF) and ischaemic stroke lesion sites. MethodsOf a local database, patients with acute first-ever ischaemic stroke confirmed by brain imaging but without pre-existing heart disease were included. The cardiac morphology and LVEF were obtained from transthoracic or transesophageal echocardiography, and impaired LVEF was categorised as mild (35%-50%), moderate (34%-25%) and severe (<25%). Patient age, stroke severity, ischaemic lesion volume, prevalence of troponin I increase (>0.1 ng/mL), atrial fibrillation and cardiac wall motion abnormalities were assessed and compared between patients with and without impaired LVEF after stroke (significance: p<0.05). A multivariate voxelwise lesion analysis correlated LVEF after stroke with sites of ischaemic lesions. ResultsOf 1209 patients who had a stroke, 231 (mean age 66.3 +/- 14.0 years) met the inclusion criteria; 40 patients (17.3%) had an impaired LVEF after stroke. Patients with impaired LVEF had higher infarct volumes (53.8 mL vs 30.0 mL, p=0.042), a higher prevalence of troponin increase (17.5% vs 4.2%, p=0.006), cardiac wall motion abnormalities (42.5% vs 5.2%, p<0.001) and atrial fibrillation (60.0% vs 26.2%, p<0.001) than patients with LVEF of >50%. The multivariate voxelwise lesion analysis yielded associations between decreased LVEF and damaged voxels in the insula, amygdala and operculum of the right hemisphere. ConclusionOur imaging analysis unveils a prominent role of the right hemispheric central autonomic network, especially of the insular cortex, in the brain-heart axis. Our results support preliminary evidence that acute ischaemic stroke in distinct brain regions of the central autonomic network may directly impair cardiac function and thus further supports the concept of a distinct stroke-heart syndrome.
CRIS-Team WoS Importer:2023-02-24

Cardiovascular autonomic dysfunction in patients with posterior circulation ischemic stroke - Wang, Ruihao; Macha, Kosmas; Koehn, Julia; Siedler, Gabriela; Winder, Klemens; Gerner, Stefan; Schwab, Stefan; Kohrmann, Martin; Hilz, Max-Josef; Kallmünzer, Bernd (JOURNAL OF THE NEUROLOGICAL SCIENCES, 2021)
CRIS-Team WoS Importer:2021-12-03

CARDIOVASCULAR AUTONOMIC MODULATION THREE MONTHS POST STROKE IMPROVES IN PATIENTS WITH ISCHEMIA IN THE RIGHT MIDDLE CEREBRAL ARTERY TERRITORY - Wang, Ruihao; Macha, Kosmas; Köhn, Julia; Marsch, Armin; Winder, Klemens; Gerner, Stefan; Koehrmann, M.; Schwab, Stefan; Kallmünzer, Bernd; Hilz, Max-Josef (INTERNATIONAL JOURNAL OF STROKE, 2020)
CRIS-Team WoS Importer:2021-01-22

Cardiovascular fingolimod effects on rapid baroreceptor unloading are counterbalanced by baroreflex resetting - Hilz, Max-Josef; Roy, Sankanika; de Rojas Leal, Carmen; Liu, Mao; Canavese, Francesca; Winder, Klemens; Hoesl, Katharina M.; Lee, De Hyung; Linker, Ralf A.; Wang, Ruihao (Neurological Sciences, 2021)
Background and purpose: Initial cardiovascular fingolimod effects might compromise baroreflex responses to rapid blood pressure (BP) changes during common Valsalva-like maneuvers. This study evaluated cardiovascular responses to Valsalva maneuver (VM)-induced baroreceptor unloading and loading upon fingolimod initiation. Patients and methods: Twenty-one patients with relapsing-remitting multiple sclerosis performed VMs before and 0.5, 1, 2, 3, 4, 5, and 6 hours after fingolimod initiation. We recorded heart rate (HR) as RR intervals (RRI), systolic and diastolic BP (BPsys, BPdia) during VM phase 1, VM phase 2 early, VM phase 2 late, and VM phase 4. Using linear regression analysis between decreasing BPsys and RRI values during VM phase 2 early, we determined baroreflex gain (BRG) reflecting vagal withdrawal and sympathetic activation upon baroreceptor unloading. To assess cardiovagal activation upon baroreceptor loading, we calculated Valsalva ratios (VR) between maximal and minimal RRIs after strain release. Analysis of variance or Friedman tests with post hoc analysis compared corresponding parameters at the eight time points (significance: p < 0.05). Results: RRIs at VM phase 1, VM phase 2 early, and VM phase 2 late were higher after than before fingolimod initiation, and maximal after 4 hours. Fingolimod did not affect the longest RRIs upon strain release, but after 3, 5, and 6 hours lowered the highest BPsys values during overshoot and all BPdia values, and thus reduced VRs. BRG was slightly higher after 3 and 5 hours, and significantly higher after 4 hours than before fingolimod initiation. Conclusions: VR-decreases 3–6 hours after fingolimod initiation are physiologic results of fingolimod-associated attenuations of BP and HR increases at the end of strain and do not suggest impaired cardiovagal activation upon baroreceptor loading. Stable and at the time of HR nadir significantly increased BRGs indicate improved responses to baroreceptor unloading. Thus, cardiovascular fingolimod effects do not impair autonomic responses to sudden baroreceptor loading or unloading but seem to be mitigated by baroreflex resetting.
CRIS-Team Scopus Importer:2021-01-29
Keywords: Baroreflex gain; Baroreflex resetting; Cardiovascular fingolimod effects; Multiple sclerosis; Valsalva maneuver

Cerebral lesions in the central pain matrix are associated with headache in multiple sclerosis - Fröhlich, Kilian; Macha, Kosmas; Siedler, Gabriela; Sekita, Alexander; Haupenthal, David; Mrochen, Anne; Wang, Ruihao; Schembs, Leah; Dörfler, Arnd; Seifert, Frank; Schwab, Stefan; Winder, Klemens (Scientific Reports, 2025)
Headache is very frequent in multiple sclerosis. However, the question whether headache is just coincidental or may be secondary due to inflammatory cerebral multiple sclerosis lesions is yet to be clarified. This study intended to evaluate the distribution of cerebral lesion sites and the potential presence of specific lesion clusters in patients with multiple sclerosis and comorbid headache using voxel-based lesion symptom mapping (VLSM). Patients with multiple sclerosis and headache were prospectively identified and included in a university neurological center between 2017 and 2023. Only patients with headache onset after first manifestation of multiple sclerosis were included. Demographic and clinical data were assessed, and lesion volumes calculated. Cerebral lesion sites were correlated voxel-wise with presence and absence of headache using non-parametric permutation testing. A cohort of multiple sclerosis patients served as controls for the VLSM-analysis. 48 multiple sclerosis patients with headache were included, as well as 92 controls without headache. Of the 48 patients with headache, 39 (81%) were female and nine (19%) were male. Mean age was significantly higher in headache patients than in controls (51 + / − 11 vs. 42 + / − 11 years, p < 0.05). EDSS, disease duration and lesion volumes did not significantly differ between both groups. Lesion overlap of all patients demonstrated a distribution of white matter lesions consistently in all subcortical brain areas. The VLSM-analysis showed associations between headache and lesion clusters in the left insula, left hippocampus and right thalamus. In our study, multiple sclerosis lesions in the left insula, left hippocampus and right thalamus were associated with headache in multiple sclerosis patients. The data therefore indicates that headache in multiple sclerosis may, in a proportion of patients, result from lesions in the central nervous systems’ pain processing network. Trial registration: No. 93_17 B, Ethics committee of the University Hospital Erlangen-Nürnberg.
CRIS-Team Scopus Importer:2025-04-01
Keywords: Cerebral lesions; Headache; Multiple sclerosis; Voxel-based lesion symptom mapping

Cerebral lesions sites in neurosarcoidosis: a lesion mapping study - Fröhlich, Kilian; Mrochen, Anne; Wang, Ruihao; Haupenthal, David; Macha, Kosmas; Siedler, Gabriela; Knott, Michael; Dörfler, Arnd; Schwab, Stefan; Winder, Klemens (Journal of Neurology, 2023)
Background and purpose: Sarcoidosis is a granulomatous disease of unknown etiology affecting the central nervous system in up to 15% of the patients. Diagnosis of neurosarcoidosis is very challenging due to the heterogeneity of its clinical manifestation. This study intended to evaluate the distribution of cerebral lesion sites and the potential presence of specific lesion clusters in neurosarcoidosis patients using voxel-based lesion symptom mapping (VLSM). Methods: Patients with neurosarcoidosis were retrospectively identified and included between 2011 and 2022. Cerebral lesion sites were correlated voxel-wise with presence and absence of neurosarcoidosis using non-parametric permutation test. Multiple sclerosis patients served as controls for the VLSM-analysis. Results: Thirty-four patients (mean age 52 ± 15 years) of whom 13 were diagnosed with possible, 19 with probable and 2 with confirmed neurosarcoidosis were identified. Lesion overlap of neurosarcoidosis patients demonstrated a distribution of white matter lesions in all brain areas, with a periventricular predilection similar to multiple sclerosis. In contrast to multiple sclerosis controls, no propensity for lesions in proximity of the corpus callosum was observed. Neurosarcoidosis lesions appeared smaller and lesion volume was lower in the neurosarcoidosis cohort. The VLSM analysis showed minor associations between neurosarcoidosis and damaged voxels in the bilateral frontobasal cortex. Conclusions: The VLSM analysis yielded significant associations in the bilateral frontal cortex, suggesting that leptomeningeal inflammatory disease with following cortical involvement is a quite specific feature in neurosarcoidosis. Lesion load was lower in neurosarcoidosis than in multiple sclerosis. However, no specific pattern of subcortical white matter lesions in neurosarcoidosis was revealed.
CRIS-Team Scopus Importer:2023-07-21
Keywords: Cerebral lesions; Neurosarcoidosis; Sarcoidosis; Voxel-based lesion symptom mapping

COMPASS 31 bladder sub-scores correlate with uroflow parameters in patients with relapsing-remitting multiple sclerosis - Wang, Ruihao; Fröhlich, Kilian; Winder, Klemens; Singer, W.; Lee, D.; Linker, R.; Hilz, Max-Josef (EUROPEAN JOURNAL OF NEUROLOGY, 2022)
CRIS-Team WoS Importer:2022-07-22

Compromised cardiovascular autonomic modulation in patient with acute ischemic stroke improves after three & six months - Wang, Ruihao; Macha, Kosmas; Köhn, Julia; Köhn, Julia; Siedler, Gabriela; Winder, Klemens; Gerner, Stefan; Schwab, Stefan; Koehrmann, M.; Kallmünzer, Bernd; Hilz, Max-Josef (EUROPEAN JOURNAL OF NEUROLOGY, 2021)
CRIS-Team WoS Importer:2021-07-23

Correction to: Neck cooling induces blood pressure increase and peripheral vasoconstriction in healthy persons (Neurological Sciences, (2020), 41, 9, (2521-2529), 10.1007/s10072-020-04349-x) - Köhn, Julia; Wang, Ruihao; de Rojas Leal, Carmen; Kallmünzer, Bernd; Winder, Klemens; Köhrmann, Martin; Kollmar, Rainer; Schwab, Stefan; Hilz, Max-Josef (Neurological Sciences, 2021)
The article “Neck cooling induces blood pressure increase and peripheral vasoconstriction in healthy persons”, written by Julia Koehn, Ruihao Wang, Carmen de Rojas Leal, Bernd Kallmünzer, Klemens Winder, Martin Köhrmann, Rainer Kollmar, Stefan Schwab and Max J. Hilz, was originally published Online First without Open Access. After publication in volume 41, issue 9, page 2521–2529 the authors decided to opt for Open Choice and to make the article an Open Access publication. Therefore, the copyright of the article has been changed to © The Author(s) 2020 and the article is forthwith distributed under the terms of the Creative Commons Attribution 4.0 International License, which permits use, sharing, adaptation, distribution and reproduction in any medium or format, as long as you give appropriate credit to the original author(s) and the source, provide a link to the Creative Commons licence, and indicate if changes were made. The images or other third party material in this article are included in the article’s Creative Commons licence, unless indicated otherwise in a credit line to the material. If material is not included in the article’s Creative Commons licence and your intended use is not permitted by statutory regulation or exceeds the permitted use, you will need to obtain permission directly from the copyright holder. To view a copy of this licence, visit http:// creat iveco mmons. org/ licen ses/ by/4.0. The original article has been corrected.
CRIS-Team Scopus Importer:2021-07-16

Incidence, temporal profile and neuroanatomic correlates of poststroke epilepsy - Winder, Klemens; Bobinger, Tobias; Seifert, Frank; Mrochen, Anne; Haupenthal, David; Knott, Michael; Dörfler, Arnd; Hilz, Max-Josef; Schwab, Stefan; Fröhlich, Kilian (Journal of Neuroimaging, 2023)
Background and Purpose: The relationship between ischemic stroke site and occurrence of poststroke epilepsy (PSE) is incompletely understood. This study intended to evaluate incidence and temporal profiles of seizures and to correlate ischemic lesion sites with PSE using voxel-based lesion symptom mapping (VLSM). Methods: Patients with imaging-confirmed first-ever ischemic stroke without prior history of epilepsy were prospectively included. Demographic data, cardiovascular risk factors, and National Institute of Health Stroke Scale (NIHSS) scores were assessed. Data on seizures and modified Rankin scale scores were determined within a 90-day period after stroke onset. Ischemic lesion sites were correlated voxel wise with occurrence of PSE using nonparametric permutation test. Age- and sex-matched patients with first-ever ischemic strokes without PSE after 90 days served as controls for the VLSM analysis. Results: The stroke database contained 809 patients (mean age: 68.4 ± 14.2 years) with first-ever imaging-confirmed ischemic strokes without history of epilep. Incidence of PSE after 90-day follow-up was 2.8%. Five additional patients were admitted to the emergency department with a seizure after 90-day follow-up. Fifty percent of the seizures occurred in the acute phase after stroke. PSE patients had higher NIHSS scores and infarct volumes compared to controls without PSE (p <.05). PSE patients had infarcts predominantly involving the cerebral cortex. The hemisphere-specific VLSM analysis shows associations between PSE and damaged voxels in the left-hemispheric temporo-occipital transition zone. Conclusions: The data indicate that PSE occurs in a small proportion of patients with rather large ischemic strokes predominantly involving the cerebral cortex. Especially patients with ischemic lesions in the temporo-occipital cortex are vulnerable to develop PSE.
CRIS-Team Scopus Importer:2023-05-19
Keywords: ischemic stroke; poststroke epilepsy; voxel-based lesion symptom mapping

PERIPHERAL PULSE MEASUREMENTS FOR THE DETECTION OF SILENT ATRIAL FIBRILLATION: RESULTS FROM THE PROSPECTIVE, CONTROLLED TRIAL "KNOW YOUR PULSE POST STROKE" - Kallmünzer, Bernd; Macha, Kosmas; Wang, Ruihao; Siedler, Gabriela; Stoll, Svenja; Marsch, Armin; Gerner, Stefan; Winder, Klemens; Koehn, J.; Schwab, Stefan; Koehrmann, M. (INTERNATIONAL JOURNAL OF STROKE, 2020)
CRIS-Team WoS Importer:2021-01-22

Quantitative sensory phenotyping in chronic neuropathic pain patients treated with unilateral L4-dorsal root ganglion stimulation - Kinfe, Thomas Mehari; von Willebrand, Nico; Stadlbauer, Andreas; Buchfelder, Michael; Yearwood, Thomas L.; Muhammad, Sajjad; Chaudhry, Shafqat R.; Gravius, Sascha; Randau, Thomas; Winder, Klemens; Maihöfner, Christian; Gravius, Nadine; et al. (Journal of Translational Medicine, 2020)
Background: In a previous study, we reported that selective dorsal root ganglion stimulation (DRGSTIM) at DRG level L4 promoted a favorable outcome for complex regional pain syndrome (CRPS) patients along with DRGSTIM-related changes of inflammatory biomarkers in blood and saliva. The impact on somatosensation is largely unknown. Herein, we assessed the quantitative sensory profile to quantify L4-DRGSTIM effects in CRPS patients. Methods: Twelve refractory CRPS patients (4 female; 8 male; mean age 69 ± 9 years) received standardized quantitative sensory testing (QST) protocol at baseline and after 3 months of unilateral L4-DRGSTIM assessing nociceptive and non-nociceptive thermal and mechanical sensitivity of the knee affected by CRPS and the contralateral non-painful knee area. Results: At baseline, CRPS subjects showed significantly increased thresholds for warmth, tactile and vibration detection (WDT, MDT and VDT) and exaggerated pain summation (WUR). After 3 months of unilateral L4-DRGSTIM all pain parameters exhibited trends towards normalization of sensitivity accumulating to a significant overall normalization for pain sensitivity (effect size: 0.91, p < 0.01), while with the one exception of WDT all non-nociceptive QST parameters remained unchanged. Overall change of non-nociceptive detection was negligible (effect size: 0.25, p > 0.40). Notably, reduction of pain summation (WUR) correlated significantly with pain reduction after 3 months of L4-DRGSTIM. Conclusions: Selective L4-DRGSTIM lowered ongoing pain in CRPS patients and evoked significant normalization in the pain domain of the somatosensory profile. Thermoreception and mechanoreception remained unchanged. However, larger randomized, sham-controlled trials are highly warranted to shed more light on effects and mechanisms of dorsal root ganglion stimulation on quantitative sensory characteristics. The study protocol was registered at the 15.11.2016 on German Register for Clinical Trials (DRKS ID 00011267). https://www.drks.de/drks_web/navigate.do?navigationId=trial.HTML&TRIAL_ID=DRKS00011267.
CRIS-Team Scopus Importer:2020-10-30
Keywords: Complex regional pain syndrome; Dorsal root ganglion stimulation; Objective measures for neurostimulation; Sensory quantitative testing

Resection of dominant fusiform gyrus is associated with decline of naming function when temporal lobe epilepsy manifests after the age of five: A voxel-based lesion-symptom mapping study - Reindl, Caroline; Allgäuer, Andrea; Kleiser, Benedict; Onugoren, Müjgan Dogan; Lang, Johannes; Welte, Tamara; Stritzelberger, Jenny; Winder, Klemens; Schwarz, Michael; Gollwitzer, Stephanie; Trollmann, Regina; Rösch, Julie; et al. (NeuroImage: Clinical, 2022)
Objective: To determine patients’ characteristics and regions in the temporal lobe where resections lead to a decline in picture naming. Methods: 311 patients with left hemispheric dominance for language were included who underwent epilepsy surgery at the Epilepsy Center of Erlangen and whose picture naming scores (Boston Naming Test, BNT) were available preoperatively and 6-months postoperatively. Surgical lesions were mapped to an averaged template based on preoperative and postoperative MRI using voxel-based lesion-symptom mapping (VBLSM). Postoperative brain shifts were corrected. The relationship between lesioned brain areas and the presence of a postoperative naming decline was examined voxel-wise while controlling for effects of overall lesion size at first in the total cohort and then restricted to temporal lobe resections. Results: In VBLSM in the total sample, a decline in BNT score was significantly related to left temporal surgery. When only considering patients with left temporal lobe resections (n = 121), 40 (33.1%) significantly worsened in BNT postoperatively. VBLSM including all patients with left temporal resections generated no significant results within the temporal lobe. However, naming decline of patients with epilepsy onset after 5 years of age was significantly associated with resections in the left inferior temporal (extent of BNT decline range: 10.8− 14.4%) and fusiform gyrus (decline range: 12.1−18.4%). Significance: Resections in the posterior part of the dominant fusiform and inferior temporal gyrus was associated with a risk of deterioration in naming performance at six months after surgery in patients with epilepsy onset after 5 years of age but not with earlier epilepsy onset.
CRIS-Team Scopus Importer:2022-08-19
Keywords: Basal temporal language area; Epilepsy surgery; Gyrus fusiformis; Lesion localization; Naming; Neuropsychological outcome

The anesthetic approach for endovascular recanalization therapy depends on the lesion site in acute ischemic stroke - Fröhlich, Kilian; Siedler, Gabriela; Stoll, Svenja; Macha, Kosmas; Kinfe, Thomas Mehari; Dörfler, Arnd; Eisenhut, Felix; Engelhorn, Tobias; Hölter, Philip; Lang, Stefan; Mühlen, Iris; Schmidt, Manuel; et al. (Neuroradiology, 2021)
Purpose Endovascular therapy (EVT) of large-vessel occlusion in acute ischemic stroke (AIS) may be performed in general anesthesia (GA) or conscious sedation (CS). We intended to determine the contribution of ischemic cerebral lesion sites on the physician's decision between GA and CS using voxel-based lesion symptom mapping (VLSM). Methods In a prospective local database, we sought patients with documented AIS and EVT. Age, stroke severity, lesion volume, vigilance, and aphasia scores were compared between EVT patients with GA and CS. The ischemic lesions were analyzed on CT or MRI scans and transformed into stereotaxic space. We determined the lesion overlap and assessed whether GA or CS is associated with specific cerebral lesion sites using the voxel-wise Liebermeister test. Results One hundred seventy-nine patients with AIS and EVT were included in the analysis. The VLSM analysis yielded associations between GA and ischemic lesions in the left hemispheric middle cerebral artery territory and posterior circulation areas. Stroke severity and lesion volume were significantly higher in the GA group. The prevalence of aphasia and aphasia severity was significantly higher and parameters of vigilance lower in the GA group. Conclusions The VLSM analysis showed associations between GA and ischemic lesions in the left hemispheric middle cerebral artery territory and posterior circulation areas including the thalamus that are known to cause neurologic deficits, such as aphasia or compromised vigilance, in AIS-patients with EVT. Our data suggest that higher disability, clinical impairment due to neurological deficits like aphasia, or reduced alertness of affected patients may influence the physician's decision on using GA in EVT.
CRIS-Team WoS Importer:2021-07-23

Voxel-wise lesion mapping of restless legs syndrome in multiple sclerosis - Fröhlich, Kilian; Knott, Michael; Hock, Stefan; Dörfler, Arnd; Seifert, Frank; Winder, Klemens (Neurological Sciences, 2022)
Objective Restless legs syndrome (RLS) is known to be associated with multiple sclerosis (MS) and may be caused by MS lesions in specific cerebral brain regions. Applying a voxel-wise lesion analysis, we tried to identify the contribution of cerebral MS lesions to RLS. Methods In this retrospective study, we established a cohort of people with MS with documented RLS and controls of people with MS without RLS matched disease severity. Diagnosis of MS and RLS was based on the current guidelines. The MS lesions were analyzed on T2-weighted magnetic resonance imaging scans (1.5 or 3 T). After manual delineation, lesion maps were converted into stereotaxic space. We generated a lesion overlap and performed a Liebermeister test with 4000 permutations to compare the absence or presence of RLS voxel-wise between patients with and without lesions in a given voxel. Results Forty of the patients with RLS and MS fulfilled the inclusion criteria. The voxel-wise analysis yielded associations between RLS and MS in the subcortex of the left gyrus precentralis. Conclusion Our voxel-wise analysis shows associations in the subcortex of the left gyrus precentralis. Thus, our data suggests that a dysfunction of the efferent motor system due to cerebral lesions may contribute to the pathophysiology of RLS in MS.
CRIS-Team WoS Importer:2022-05-20